Functional and physical capacity indicators of kayakers racing 1000, 500, and 200 m distances: a randomized study - Diachenko, A.; Rusanova, O.; Huang, Z.; Gao, X.; Guo, J.; Ye, C. (Journal of Physical Education and Sport, 2021)
The article proposes a systematic approach to modeling the strength and capabilities of qualified kayakers by developing and implementing generalized, group and individual models of readiness. Participants. Depending on the purpose of the research phase, the theoretical and experimental parts of the research were conducted at different training periods at the national aquatic sports raining centers in Rizhao. 120 junior kayakers of 16-17 years old and 180 qualified kayakers of 19-23 years old are in the process of assessing the level of functionality, among them a group of elite athletes, the members of the Chinese national team. Results: The generalized models include the characteristics of young qualiied kayakers who are in the process of preparing for higher achievements. Interpretation of power and capacity characteristics of aerobic and anaerobic energy supply (VO2 max rel, VO2 max abs, MAOD, VO2 · HR-1, VE · V?O2-1, La) and ergometric power (30 s; AT, VO2 max, T VO2 max) is aimed at improving the efficiency of selection and sports orientation for kayaking. The group models contain the characteristics of qualified kayakers specializing in distances of 200 m, 500 m and 1000 m. The interpretation of the characteristics of aerobic and anaerobic energy supply (VO2 max rel, VO2 max abs, VE · V?O2-1, La) and ergometric power (W ergometric power) work capacity in the test 30 s. The ergometric power work in the test 4 min) is aimed at assessing the level of readiness, search for reserves to improve special performance, correction of the training process with paddlers` specialization. Individual models include the quantitative characteristics of elite kayakers, having the highest (unique) individual indicators.